2000
DOI: 10.1038/labinvest.3780137
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of CD44 Expression in Prostate Cancer by Hypermethylation of the CD44 Promoter Region

Abstract: SUMMARY:Loss of the CD44 transmembrane glycoprotein in primary prostate cancer has been shown to be associated with unfavorable clinical behavior. Moreover, the majority of prostate cancer metastases lack expression of this molecule. The mechanism of CD44 silencing in prostate cancer was investigated using both patient material and in vivo-propagated human prostate cancer xenografts. In 9 of 11 lymph node metastases of prostate cancer, we demonstrated by methylation-sensitive restriction enzyme digestion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 24 publications
1
27
1
Order By: Relevance
“…These changes were verified by sodium bisulfite sequencing as above, which revealed consistent (100% of clones sequenced) loss of methylation at two sites in the CD44 promoter (Fig. 3D), one of which included an SP1 site that had previously been reported to be hypermethylated in other cell lines (12). Transfection with mutant Brg1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes were verified by sodium bisulfite sequencing as above, which revealed consistent (100% of clones sequenced) loss of methylation at two sites in the CD44 promoter (Fig. 3D), one of which included an SP1 site that had previously been reported to be hypermethylated in other cell lines (12). Transfection with mutant Brg1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When these cells were transfected with Brg1 or Brm, endogenous CD44 transcription was induced (7,8). Interestingly, CD44 transcription is silenced in a number of cancer cell lines by hypermethylation of CpG islands within the CD44 promoter that normally remain unmethylated at all times (10)(11)(12)(13)(14). Here, we tested if transcriptional activation by Brg1 and Brm involves loss of methylation of CpG islands in promoter sequences of both the CD44 gene and another gene whose transcription is often silenced by DNA methylation, Ecadherin (15).…”
Section: Introductionmentioning
confidence: 99%
“…Strikingly, prostate cancers lose the basal cell marker p63 so consistently that its absence can be used for diagnostic purposes [156]. Similarly, the frequently hypermethylated MDR1 [21,157] and CD44 [158][159][160] genes are normally expressed in basal cells. Like GSTP1 hypermethylation (Fig.…”
Section: Stem Cell Maintenancementioning
confidence: 99%
“…255 Loss of CD44 expression is associated with increased grade and stage of PC. 256,257 No metastases express CD44 strongly, and only 14% of metastases expressed even low levels of immunohistochemically detectable CD44. In nine of 11 lymph node metastases of PC, Verkaik et al 257,258 demonstrated by methylation-sensitive restriction enzyme digestion that the promoter region of the CD44 gene is hypermethylated, indicating that this may represent a major mechanism of CD44 silencing.…”
Section: Cd44 Metastasis Suppressor Genementioning
confidence: 99%
“…256,257 No metastases express CD44 strongly, and only 14% of metastases expressed even low levels of immunohistochemically detectable CD44. In nine of 11 lymph node metastases of PC, Verkaik et al 257,258 demonstrated by methylation-sensitive restriction enzyme digestion that the promoter region of the CD44 gene is hypermethylated, indicating that this may represent a major mechanism of CD44 silencing. Transfection-induced expression of CD44 in the highly metastatic AT3.1 rat PC cell line greatly suppressed its metastatic ability to the lungs, without suppression of in vivo growth rate or primary tumorigenicity.…”
Section: Cd44 Metastasis Suppressor Genementioning
confidence: 99%